HUBUNGAN KRISIS IKLIM DAN KONFLIK KOMUNAL : ANALISIS KEKERASAN DI SAHEL - Mutiara Nursukma Wulandari; Debora Fany Ilfi Nurdiana; Marsya Ade Nabila; Zaky Ismail (Frequency of International Relations (FETRIAN), 2025)
The Sahel region of Africa has experienced an increase in communal conflict in the last two decades. This research aims to understand the extent to which the climate crisis has contributed to the emergence of violence in the region. Changes in rainfall patterns, prolonged droughts and land degradation have exacerbated struggles over resources such as water and pasture between farming and pastoralist groups. This research uses a descriptive qualitative approach through content analysis. Data sources were obtained from reports of international organizations (such as the UN, FAO, and ICRC), scientific journal articles, and global conflict databases. The data were analyzed to identify patterns of relationships between climate change phenomena and communal conflict dynamics. The results of the analysis show that the climate crisis is not a single cause, but a trigger factor that exacerbates pre-existing socio-economic tensions, such as marginalization of ethnic groups, weak local governance, and unequal access to resources. In other words, the climate crisis acts as a “threat multiplier” that increases the risk of conflict in an already vulnerable region. The research recommends a holistic approach to conflict management in the Sahel, combining climate adaptation policies, inclusive development and strengthening local institutions.